Management of hypertension and diabetes mellitus by cardiovascular and endocrine physicians: a China registry. Issue 8 (August 2016) - Song, Jie; Sheng, Chang-Sheng; Huang, Qi-Fang; Li, Li-Hua; Ma, Chang-Sheng; Guo, Xiao-Hui; Ji, Li-Nong; Wang, Ji-Guang
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: We investigated hypertension and diabetes mellitus in two management settings, namely cardiology and endocrinology, and their associations with albuminuria while accounting for the management of these two diseases. Methods: Our multicentre registry included patients (≥20 years) seen for hypertension in cardiology or for diabetes mellitus in endocrinology. We administered a questionnaire and measured blood pressure, glycosylated haemoglobin A1c and albuminuria. Results: Presence of both hypertension and diabetes was observed in 32.9% of hypertensive patients in cardiology ( n  = 1291) and 58.9% of diabetic patients in endocrinology ( n  = 1168). When both diseases were present, the use of combination antihypertensive therapy [odds ratio (OR) 0.31, P  < 0.0001] and inhibitors of the renin–angiotensin system (OR 0.66, P  = 0.0009) was less frequent in endocrinology than cardiology, and the use of combination antidiabetic therapy (OR 0.16, P  < 0.0001) was less frequent in cardiology than endocrinology. The control of hypertension and diabetes, however, was not different between the two management settings ( P  ≥ 0.21), regardless of the therapeutic target (SBP/DBP < 140/90 or 130/80 mmHg and glycosylated haemoglobin A1c <7.0 or 6.5%). The prevalence of albuminuria was higher ( P  ≤ 0.02) in the presence of both diseases (23.3%) than those with either hypertension (12.6%) or diabetes alone (15.9%). Conclusion: Hypertension and diabetes mellitus were often jointly present, especially in the setting of endocrinology. The management was insufficient on the use of combination antihypertensive therapy and inhibitors of the renin–angiotensin system in endocrinology and for combination antidiabetic therapy in cardiology, indicating a need for more intensive management and better control of both clinical conditions.